Courage the cowardly dog. Season one [videorecording (DVD)] - Dilworth, John R., 1963- (Cartoon Network hall of fame., 2010)
The things he does for love! Welcome to the middle of Nowhere, Kansas. Population: one kind old lady, one crabby old man, one timid dog, and all sorts of creepy creatures, scary monsters, and crazed villains! It's a living nightmare for poor Courage, who faces these unthinkable dangers with his body shaking and his tail between his legs.